2014
DOI: 10.5817/cpr2014-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Gradient of algal and cyanobacterial assemblages in a temporary lake with melting water at Solorina Valley, James Ross Island, Antarctica

Abstract: The aim of presented study is to contribute to species list of algae, cyanobacteria and diatoms from moist localities of James Ross Island, Solorina Valley (63° 53' S, 57° 48' W) in particular. In 2012, samples of microbiological mats were taken from a bottom of shallow depression close to a seashore line. The sampling site has been filled with melting water from glacier for some weeks preceding the collection. On collection date, however it was dried out. The samples were analysed using optical microscopy app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Our samples reported in this study, i.e. those collected from streams and seepages fed by melting snow at Komarek slopes showed lower taxonomical diversity than the earlier samples from lakes (Skácelová et al 2013) and soil crusts (Skácelová et Barták 2014) from James Ross Island (Ha-wes et Brazier 1991, Kopalová et al 2012. in their study determined relatively broad spectrum of cyanobacterial species in seepages at Komarek slopes.…”
Section: Discussioncontrasting
confidence: 50%
“…Our samples reported in this study, i.e. those collected from streams and seepages fed by melting snow at Komarek slopes showed lower taxonomical diversity than the earlier samples from lakes (Skácelová et al 2013) and soil crusts (Skácelová et Barták 2014) from James Ross Island (Ha-wes et Brazier 1991, Kopalová et al 2012. in their study determined relatively broad spectrum of cyanobacterial species in seepages at Komarek slopes.…”
Section: Discussioncontrasting
confidence: 50%
“…Within the last three decades, biodiversity studies have been performed here, focused on freshwater diatoms (Kopalová et al . 2013), terrestrial algae (Skácelová & Barták 2014), cyanobacteria and lichens (Lewis Smith & Øvstedal 1994) and mosses (BAS moss database ‐ see Antarctic Plant Database in other sources). The microclimate has the following temperature characteristics (measured 2 m above the ground): −33.1 °C (annual minimum), 9.3 °C (annual maximum) and −9.8 °C annual mean (data from Elster et al .…”
Section: Methodsmentioning
confidence: 99%
“…Several shallow depressions are located over the terrase. They are filled by meltwater at the begining of austral summer season and rich in microbiological mats formed by tens of algal and cyanobacterial species (Skácelová and Barták 2014). The regolith from Solorina Valley was analyzed by Coufalík et al (2015), who revealed low mercury levels originated from weathering of bedrock.…”
Section: Ecology and Distributionmentioning
confidence: 99%